MASTERING IDIOMATIC EXPRESSION AND ITS RELATIONSHIP WITH READING COMPREHENSION OF FIFTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT UNISMA - Miswak Miswak (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
AbstractThe aim of this research was to find out whether there is relationship between mastering idiomatic expressions with reading comprehension of fifth semester students of English department at University of Islam Malang. The population and the sample of this research were from fifth semester students and it was made up of 30 homogeneous students in the F class and was chosen using the cluster sampling method. The instrument from the idiom test which was adopted from online and offline source, and consist of 25 questions with multiple choice answers. Then, reading comprehension test consist of 25 multiple choice questions, contains several of idioms in the text which is adopted from reading TOEFL test. The result showed that the mean of the idiom mastery scores for the participants is 69.03 and the standard deviation is 5.430 and the mean of the reading comprehension scores for the participants is 78.40 and the standard deviation is 3.971, for the result Pearson-Product Moment Correlation indicates that the correlation coefficient table of df at 5% significance is considered to be .374. It shows that it is lower than the correlation coefficient table score, which is .303 < .374, based on the correlation coefficient of the measurement, which was .303. This means that H0 is accepted and H1 is rejected. Namely, there is no significant relationship between students who have good ability in mastering idioms and students’ comprehension of reading skill. Keyword: idiomatic expression, reading comprehension, relationship